Strategi Minat Beli Generasi Z Pada TikTok Shop di Kota Palembang - William Efrans Oktayandi; Herry Widagdo (MDP Student Conference, 2026)
This study aims to examine the influence of content marketing, influencer marketing, brand image, and sales promotion on Generation Z’s purchase intention among TikTok Shop user in Palembang City. This research employs a quantitative approach using a survey method. The sampling technique applied was probability sampling with a cluster sampling method, resulting in 240 respondents. Data were analyzed using multiple linear regression with SPSS version 26. The partial test result indicate that content marketing, influencer marketing, brand image, and sales promotion each have a positive and significant effect on purchase intention. Simultaneously, all independent variables significantly influence purchase intention. This study concludes that effective digital marketing strategies implemented through TikTok Shop play an important role in increasing Generation Z’s purchase intention.